Políticas públicas para a primeira infância em Sorocaba (SP): limites e possibilidades das articulações feitas pelo Conselho Municipal de Educação (CMESO) - Moreira, Danieli Casare da Silva (Universidade Federal de São Carlos, 2022)
This study aims to investigate the performance of the Municipal Education Council of Soro-caba (CMESO) in relation to public policies for Early Childhood Education regarding educational management processes within the Municipal Education System (SME). For that, initially, a contextualization about the genesis of the municipal education councils is exposed, as well as the constitution, trajectory and dynamics of functioning of the CMESO. Priority was also given to understanding what were the proposals for public policies for early childhood guided by the collegiate and their impacts at this stage of teaching. This research was methodologically based on the qualitative approach and documental analysis of minutes, opinions and deliberations of the CMESO in the time frame from 2018 to 2020. As a result, several topics addressed by this Council in relation to Early Childhood Education and its referrals were identified. , namely: discontinuity of Public Policy action projects and programs that culminated in CMESO Deliberation 02/2018; prohibition of the adoption of apostille for Education in the Municipality enacted by CMESO Resolution 06/2018; adult/child proportionality for early childhood education with CMESO Resolution 03/2018; as well as pedagogical proposals and definitions of actions by the municipality for early childhood education in the pandemic. In this sense, it is understood that the potential of the CMESO encompasses: the regulation and organization of the Education System, the establishment of guidelines for its planning, execution and evaluation. The Councils also play a fundamental role in the democratic management of the Teaching System and are committed to building social quality education. The challenges encountered involve the articulation and mediation of the demands of education by the local civil society together with the managers of the municipal public power. It is argued that the CMESO is a body attentive to the reality of the municipality and that fulfills its fundamental role in the democratic management of the Education System, based on the commitment to build quality education for all, aiming to guarantee equality and equity.
Public polices for early children in Sorocaba (SP): limits and possibilities of the articulations made by the Municipal Council of Education (CMESO)
Keywords: Primeira infância; Políticas públicas; Conselho Municipal de Educação; Educação; Education; Early childhood; Public policy; City council of education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO